Changes in Bacterial and Fungal Quality During Storage of Smoked, Esomus danricus of Manipur - H., Lilabati; W., Vishwanath; M., Shymkesho Singh (Fishery Technology, 2025)
Total plate counts of bacteria (TPC) and fungi (TFC) gradually decreased with the decrease of moisture content in smoked Esomus danricus during storage of the fish in bamboo baskets. The counts increased with the increase of humidity of the environment and the moisture content of the fish. Coliforms were not detected after 30 days of storage and Staphylococcus aureus and feacal Streptococci were not detected after 60 days of storage. Â£. coli and Salmonella were not detected in the present analysis. Xerophilic fungi, viz., Aspergillus candidus, Aspergillus fumigatus, Aspergillus niger, Aspergillus sydowii and Penicillium chrysogenum were observed during storage of the fish. A. niger and A. candidus were dominant in April, May and June, whereas Aspergillus flavipes was dominant in July and August. Growth of fungi was rapid in the rainy season. Smoked E. danricus was in unacceptable condition after storage for 120 days.